Registro De Bienes Culturales Muebles Para El Análisis Arqueológico De Grupos Sociales Precolombinos. Estudio De Caso: Puñay, Cantón Chunchi, Provincia De Chimborazo, Ecuador - Santillán, Carlos Arturo Jara; Merino, Christiam Paúl Aguirre; Bernal, Catalina Margarita Verdugo; Moyota, Paulina Beatriz Díaz; Salazar, Sandra Patricia Miranda; Zambrano, Ginno Sidney Jarrín; Viveros, Clara Etelvina Amanta (European Scientific Journal, ESJ, 2017)
The aim of this study is to present the results of the identification of the cultural styles, social occupations, and cultural affiliates of archaeological sites such as Paccha, Piñancay, Puñay, and Joyaczhi that conforms to the archaeological area, Puñay. The objective of this study is to keep an archaeological record of the movable cultural property of tourist sites. This is done through the cataloging and characterization of movable property. In cataloging, the records of the archaeological assets of the INPC are applied. Also, in characterization, the methodology was considered as the Crockery for the determination of the Ceramic Cultural styles and the color of the external and internal pulp. In addition, the core of the Munsell tables was considered. The research allows the identification of 10 ceramic cultural styles in Paccha, 8 in Piñancay, 10 in Puñay sector, and 3 in Joyaczhi through typology and decorative techniques. Also, they are visualized chronologies which are related to the social contexts in which these archeological properties are materialized. The ceramic styles established for the archaeological area belongs to the Integration Period of the pre-Columbian culture Cañari 800- 1530d.C.